A Pre-Printed Reporting System for Multiple Data in Clinical Bacteriology - Graevenitz, A. v. (Methods of Information in Medicine, 1969)
A system is presented which enables the Bacteriology Laboratory to report pure or mixed cultures with quantitations and antimicrobial sensiti vities on ‘ one final form. It consists of a Requisition Slip, listing patient data and specimen sources, and a Report Form - both of which catry at least one carbon or NCR paper copy. The Report Form contains a blank for a mount of the Requisition Slip, a list of bacteria with quantities and sensitivities for each organism, and a flow sheet for the workUp. The forms may be completed with a pen or designed as punchards.